2020
DOI: 10.1007/s00253-020-10821-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phosphorus source and the nature of nitrogen substrate on the biomass production and lipid accumulation in oleaginous Mucoromycota fungi

Abstract: Oleaginous filamentous fungi grown under the nitrogen limitation, accumulate high amounts of lipids in the form of triacylglycerides (TAGs) with fatty acid profiles similar to plant and fish oils. In this study, we investigate the effect of six phosphorus source concentrations combined with two types of nitrogen substrate (yeast extract and ammonium sulphate), on the biomass formation, lipid production, and fatty acid profile for nine oleaginous Mucoromycota fungi. The analysis of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 59 publications
(75 reference statements)
3
35
0
Order By: Relevance
“…Only two observations could be considered as significant—increase of biomass under higher Zn ion availability and Ca deficiency. Moreover, under Pi conditions lower than the reference (Pi0.5 and Pi0.25), K and Na ions were compensated with KCl and NaCl salts in order to provide the same Na and K amounts as in the reference Pi1 condition [ 43 , 44 ]. It has been reported that chlorides could have negative effect on the mycelium formation of some fungi [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two observations could be considered as significant—increase of biomass under higher Zn ion availability and Ca deficiency. Moreover, under Pi conditions lower than the reference (Pi0.5 and Pi0.25), K and Na ions were compensated with KCl and NaCl salts in order to provide the same Na and K amounts as in the reference Pi1 condition [ 43 , 44 ]. It has been reported that chlorides could have negative effect on the mycelium formation of some fungi [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spores were collected from agar plates using 10 ml of saline solution and a bacteriological loop. The composition of the reference medium, used and modified in our previous studies [ 27 , 43 , 44 , 45 ], was the following: 80 g/L of glucose, 1.5 g/L of (NH 4 ) 2 SO 4 , 7 g/L of KH 2 PO 4 , 2 g/L of Na 2 HPO 4 , 1.5 g/L of MgSO4·7H2O, 0.1 g/L of CaCl2·2H2O, 0.008 g/L of FeCl3·6H2O, 0.001 g/L of ZnSO4·7H2O, 0.0001 g/L of CoSO4·7H2O, 0.0001 g/L of CuSO4·5H2O, 0.0001 g/L of MnSO4·5H2O, where the listed concentrations of the metal ions Ca, Cu, Co, Fe, Mg, Mn, and Zn were assigned as reference concentration and marked as “R” ( Table 1 ). The higher—1000; 100; 10 × R and lower—0.1; 0.01 and 0 × R concentrations of the metal ions were assessed in the study as described in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations